1981
DOI: 10.1002/jnr.490060309
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of taurine on the light‐induced disruption of isolated frog rod outer segments

Abstract: Isolated frog rod outer segments (ROS) incubated in a Krebs-bicarbonate medium, and illuminated for 2 h, show a profound alteration in their structure. This is characterized by distention of discs, vesiculation, and a marked swelling. The light-induced ROS disruption requires the presence of bicarbonate and sodium chloride. Replacement of bicarbonate by TRIS or HEPES protects ROS structure. Also, substitution of sodium chloride by sucrose or choline chloride maintains unaltered the ROS structure. Deletion of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…54]. These observations suggest that taurine is involved in maintaining the structural in tegrity of photoreceptor outer segments, a conclusion supported by the observation that murine prevents light-induced damage to iso lated frog outer segments [46].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…54]. These observations suggest that taurine is involved in maintaining the structural in tegrity of photoreceptor outer segments, a conclusion supported by the observation that murine prevents light-induced damage to iso lated frog outer segments [46].…”
Section: Introductionsupporting
confidence: 66%
“…47], Zinc, which is con centrated in the retina [19]. has been impli cated in the maintenance of normal cell vol ume and ion balance [46].…”
Section: Discussionmentioning
confidence: 99%
“…Less intense taurine immunoreactivity found in the rod outer segments of the ayu might depend on the fixation process under light adaptation. In agreement with the view by LOMBARDINI (1991), the present results of the light microscopic immunolocalization of taurine in the pineal and retinal photoreceptors suggest a role based on the shielding effects of taurine on the outer segments exposed to toxic levels of light and chemicals (PASANTES-MORALES et al, 1981;CRUZ, 1984, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Since it has been suggested that taurine transport to the retina is regulated by pigment epithelium (35) and it is well-known that photoreceptor cells have well-de veloped ability for renewal of the cell membrane (36), infusion of taurine, therefore, is thought to exert a be neficial effect on the regenerative function of photore ceptor cells by recovering the taurine concentration in the retina via the pigment epithelium. This considera tion would be supported by the findings that light de privation has reduced the severity of ERG abnormali ties in GES-treated rats (30,33) and that taurine pro tects against light-induced disruption in the rod outer segment (8).…”
Section: Discussionmentioning
confidence: 79%
“…Retina is one of the sites that take up taurine with a high affinity (2)(3)(4). It has been reported that the release of taurine from a retinal preparation is induced by light stimulation (5), electrical stimulation to photoreceptor cells (6) or addition of K+ ions to the medium (7), and that taurine exhibits protective effects against the degeneration of photoreceptor cells caused by light stimulation (8), superoxide (9) or osmotic im balance (10). Therefore, taurine is thought to be re leased by certain light stimuli and to exhibit a protec tive role against photochemical damage of the photore ceptor membrane (11,12).…”
mentioning
confidence: 99%